Development of Primer Panels for Whole-Genome Amplification and Sequencing of Human Seasonal Coronaviruses: hCoV-OC43, hCoV-HKU1, hCoV-229E, and hCoV-NL63 - Tamila Musaeva; Artem Fadeev; Maria Pisareva; Veronika Eder; Andrey Ksenafontov; Margarita Korzhanova; Valery Tsvetkov; Alexander Perederiy; Irina Kiseleva; Daria Danilenko; Dmitry Lioznov; Andrey Komissarov (Viruses)
Human seasonal coronaviruses (hCoVs) are a group of viruses that affect the upper respiratory tract. While seasonal patterns and the annual variability of predominant hCoV species are well-documented, their genetic and species diversity in St. Petersburg and across Russia remains largely unexplored. In this study, we developed a two-pool, long-amplicon (900–1100 bp) PCR primer panel for the whole-genome sequencing of four seasonal hCoV species. The panel was validated using nasopharyngeal swab samples collected within the Global Influenza Hospital Surveillance Network (GIHSN) project. Over a period of six epidemiological seasons from 2017 to 2023, we retrospectively analyzed 14,704 nasopharyngeal swabs collected from patients hospitalized in St. Petersburg clinics. Of these samples, 5010 (34.07%) tested positive for respiratory viruses, with 424 (2.88% of all samples) identified as seasonal human coronaviruses. The assessment of species diversity showed that predominant hCoV species alternate between seasons. Whole-genome sequences for 85 seasonal human coronaviruses (hCoVs) with >70% genome coverage were obtained, including 23 hCoV-OC43, 6 hCoV-HKU1, 39 hCoV-229E, and 17 hCoV-NL63. These represent the first near-complete genomes of seasonal hCoVs from the Russian Federation, addressing a significant gap in the genomic epidemiology of these viruses. A detailed phylogenetic analysis of the sequenced genomes was conducted, highlighting the emergence of hCoV-229E subclades 7b.1 and 7b.2, which carry numerous substitutions in the Spike protein. Additionally, we sequenced a historical hCoV-229E isolate collected in the USSR in 1979, the oldest sequenced 229E virus from Eurasia, and demonstrated that it belongs to Genotype 2. The newly developed PCR-based sequencing protocol for seasonal hCoVs is straightforward and well-suited for genomic surveillance, providing a valuable tool to enhance our understanding of the genetic diversity of human seasonal coronaviruses.